DESIGN AND SIMULATION OF THE RADAR CROSS-SECTION REDUCTION ANTENNA OPERATING IN THE 28 GHz-BAND OF 5G - Ngoc, Tran Thi Bich (HUIT Journal of Science, 2023)
The main idea of this work is to design and simulate a microstrip antenna with reducing Radar Cross-Section (RCS) accomplished in 28 GHz-band for 5G. The design is based on a combination of Frequency Selective Surfaces (FSSs) and a microstrip antenna. In particular, the RCS reduction can be realized by using the FSS in the place of the metal ground. The resonant frequency can be at the 28 GHz band. The reflection coefficient of the proposed structure is better (about 31 dB) than nearly 21 dB for the reference antenna. The RCS value decreases significantly in the frequency ranges of 24-32 GHz. Additionally, the radiation performances are mostly maintained. In the paper, the simulation results are performed using the software program CST Microwave Studio.